2020
DOI: 10.3390/ijerph17228625
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Household Food Garden Intervention on Food Security in Lesotho

Abstract: Food insecurity is a challenge in the developing world, where many are finding healthy food inaccessible due to poverty. A pre-test, post-test design was applied to determine the impact of a vegetable gardening intervention in 25 experimental and 25 control households in Lesotho. Information about sociodemographic conditions and indicators of food security was collected by trained fieldworkers. As evidenced by the Living Poverty Index of 2.5, the sample was characterized by high levels of poverty. Although alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In Lesotho, a region where food sharing is a common cultural practice, it was reported that a household gardening intervention reduced the proportion of households with low DD from 28% to 12%. The intervention also resulted in small increases in the intake of vitamin A-rich vegetables and other vegetables [ 42 ]. Thus, promotion of appropriately designed home gardening interventions could be a simple, culturally appropriate way to improve DD by home-grown foods being available for BEB.…”
Section: Discussionmentioning
confidence: 99%
“…In Lesotho, a region where food sharing is a common cultural practice, it was reported that a household gardening intervention reduced the proportion of households with low DD from 28% to 12%. The intervention also resulted in small increases in the intake of vitamin A-rich vegetables and other vegetables [ 42 ]. Thus, promotion of appropriately designed home gardening interventions could be a simple, culturally appropriate way to improve DD by home-grown foods being available for BEB.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown unconditional cash transfers improve food security and mental health [138,139]. Community gardens are another initiative that can be implemented to diversify diets further and increase the consumption of foods and vegetables [140,141]. Increased training on agricultural activities, especially agroecological practices, could help improve nutrition awareness [142], healthy diets and kitchen gardening [143].…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 99%
“….evious studies in Lesotho have shown that Basotho women lack nutrition-related knowledge and that their dietary intake is largely inadequate. As a result, their nutritional status is challenged and they present with high levels of malnutrition, including both undernutrition, overnutrition, and micro-nutrient deficiencies (8)(9)(10). Although undocumented nutrition-related initiatives have been undertaken in Lesotho (including radio talks and presentations at women's groups), most of these are fragmented and focused on single topics (8).…”
mentioning
confidence: 99%